2015
DOI: 10.1152/ajprenal.00471.2013
|View full text |Cite
|
Sign up to set email alerts
|

ENaC inhibition stimulates HCl secretion in the mouse cortical collecting duct. I. Stilbene-sensitive Clsecretion

Abstract: Inhibition of the epithelial Na+ channel (ENaC) reduces Cl− absorption in cortical collecting ducts (CCDs) from aldosterone-treated rats and mice. Since ENaC does not transport Cl−, the purpose of the present study was to explore how ENaC modulates Cl− absorption in mouse CCDs perfused in vitro. Therefore, we measured transepithelial Cl− flux and transepithelial voltage in CCDs perfused in vitro taken from mice that consumed a NaCl-replete diet alone or the diet with aldosterone administered by minipump. We ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Because of the prominent effects of ClC-5 in the PT, the physiological role of this transporter in the TAL and ICCD seems to be underrated. However, expression of ClC-5 in these segments is well documented ( Günther et al, 1998 ; Luyckx et al, 1998 ; Devuyst, 1999 ; Sakamoto et al, 1999 ; Nanami et al, 2015 ; Ogawa et al, 2017 ; see Figure 1 ). Several studies demonstrate that this expression has a physiological impact.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Because of the prominent effects of ClC-5 in the PT, the physiological role of this transporter in the TAL and ICCD seems to be underrated. However, expression of ClC-5 in these segments is well documented ( Günther et al, 1998 ; Luyckx et al, 1998 ; Devuyst, 1999 ; Sakamoto et al, 1999 ; Nanami et al, 2015 ; Ogawa et al, 2017 ; see Figure 1 ). Several studies demonstrate that this expression has a physiological impact.…”
Section: Discussionmentioning
confidence: 98%
“…Based on the homology between proteins of the CLC family, we hypothesized that barttin might be also able to regulate the function and localization of ClC-5. Remarkably, expression of ClC-5 has been detected not only in the PT, which is devoid of barttin, but also in kidney segments with significant barttin expression such as the thick ascending limb of the Henle’s loop (TAL), and in intercalated cells of the collecting duct (ICCD) ( Günther et al, 1998 ; Luyckx et al, 1998 ; Devuyst, 1999 ; Sakamoto et al, 1999 ; Nanami et al, 2015 ; Ogawa et al, 2017 ;Figure 1A ).…”
Section: Introductionmentioning
confidence: 99%
“…As such, ENaC blockade must alter Cl Ϫ exchange or channel activity either by changing the release of a signaling molecule that regulates this transporter/channel or by modulating the driving force for Cl Ϫ movement mediated by another Cl Ϫ transport mechanism. While the Cl Ϫ transport mechanism targeted by ENaC inhibition is unknown, it does not appear to be mediated by pendrin, ClC-5, or CFTR (46,51,52). Amiloride-sensitive Cl Ϫ absorption may occur instead through paracellular Cl Ϫ transport or through transcellular Cl Ϫ transport mediated by an electrogenic Cl Ϫ exchanger or a Cl Ϫ channel.…”
Section: Pendrin Localizes To Type B and Non-a Non-b Intercalated Cementioning
confidence: 99%
“…1 ), which is expressed on the apical plasma membrane and is upregulated in models of metabolic acidosis [ 24 , 25 ]. In the type A intercalated cell, this active H + secretion occurs in parallel with secretion of Cl − , although the mechanism for Cl − secretion is not well understood [ 26 29 ].…”
Section: The Role Of Intercalated Cell Subtypes In Acid-base Regulatimentioning
confidence: 99%
“…ENaC blockade changes Cl − transport or channel activity either through paracrine signaling or by altering the driving force of Cl − movement. While the mechanism by which ENaC inhibition changes Cl − transport is not known, recent studies have shown that it does not involve pendrin, ClC-5, or CFTR [ 5 , 26 , 48 ]. Amiloride-sensitive Cl − absorption may involve paracellular Cl − transport or transcellular transport mediated by an electrogenic Cl − exchanger.…”
Section: Pendrin Localizes To Type B and Non-a Non-b Intercalated Cementioning
confidence: 99%